2000
DOI: 10.1007/pl00007070
|View full text |Cite
|
Sign up to set email alerts
|

Systems for therapeutic angiogenesis in tissue engineering

Abstract: The goals in tissue engineering include the replacement of damaged, injured, or missing body tissues with biologically compatible substitutes. To overcome initial tissue-mass loss, improved vascularization of the regenerated tissue is essential. Two pathways of tissue neovascularization are known: vasculogenesis, the in situ assembly of capillaries from undifferentiated endothelial cells (EC), and angiogenesis, the sprouting of capillaries from preexisting blood vessels. Recent advances in our understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
101
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(105 citation statements)
references
References 96 publications
3
101
0
1
Order By: Relevance
“…[27][28][29] Data on neovascularization of biomaterials are based today mainly on semiquantitative histological studies. 10,19,29,30 The dynamic temporal course of neovascularization was previously evaluated by means of magnetic resonance imaging techniques in animals 31 as well as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Data on neovascularization of biomaterials are based today mainly on semiquantitative histological studies. 10,19,29,30 The dynamic temporal course of neovascularization was previously evaluated by means of magnetic resonance imaging techniques in animals 31 as well as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…23 To create a vascularized scaffold, a number of methods have been proposed. 24,25 One approach involves the transplantation of ECs in an effort to engineer a vascular network from these cells, rather than waiting for host-blood-vessel ingrowth. 26 However, independently of the adopted approach to accelerate vascularization, all of them will involve directly or indirectly ECs.…”
mentioning
confidence: 99%
“…1 Tissue engineering by stem cell therapy for the replacement of lost or damaged tissue with biologically compatible substitutes is a promising therapy for cardiac repair. 2 Recent evidence in animal models has shown that both embryonic and adult-derived stem cells have the capacity to differentiate into cardiovascular cell types including cardiomyocytes (CMC) and to improve cardiac function when transplanted after cardiac injury. 3,4 These findings lead to several ongoing human clinical trials.…”
mentioning
confidence: 99%